The Risk of Land Degradation in Areas Impacted by Tailings Mudflows: A Legal and Economic Assessment - de Carvalho Medeiros, Lucimar; de Moura, Maíse Soares; Navarro, Isadora Fonseca [UNESP]; Fernandes, Luís Felipe Sanches [UNESP]; Pacheco, Fernando António Leal [UNESP]; da Costa, Adriana Monteiro [UNESP] (Wiley, 2025)
Accidents involving tailings dams are threatening because of their potential impacts. In many countries, despite the existence of legislation the population lives with the insecurity of potential dam breaks. Using Minas Gerais state in Brazil as an example, the aforementioned insecurity applies to hundreds of tailings dams, specifically the Vargem Grande dam of Vale mining company. The area affected by a dam failure is set through legal-administrative instruments called “flood patches.” The purpose of this study was to analyze these patches, using the Vargem Grande dam as example, and assess the possible land degradation impacts of a failure, focused on the flooded native vegetation. The assessment resorted to the VERA—Economic Valuation of Environmental Resources method. The results exposed the potential destruction of 200 ha of Atlantic Forest and 55 ha of Cerrado vegetation within the flood patches. However, the simulated outcomes also reveal a significant decline in the flood patches in a short period (from 4.60 km2 in 2022 to 3.05 km2 in 2023), related with dam-decommissioning risk-reduction works allegedly implemented or to be implemented by the mining company. This reduction can be misleading because decommissioning works are legal-administrative issues frequently used by the mining companies to minimize their responsibilities in the case of tailings dam breakup. It is worth mentioning that the patch reduction led to a convenient drop in the VERA results, from nearly 74 to 53 million dollars. Therefore, the official protocol used to delineate the flood patches must be improved to allow a more realistic evaluation. In that regard, the changes to flood patches overtime must be better defined in the legislation, namely through inclusion of potentially affected soil- and water-bearing ecosystem services. Effective monitoring of dam-decommissioning works is also paramount for a true evaluation of land degradation in the impacted areas.
Keywords: dam breakup; environmental impacts; flood patches; native vegetation; tailings dams